Thiosulfate promotes hair growth in mouse model. Issue 1 (2nd January 2019) - Maekawa, Motoko; Ohnishi, Tetsuo; Balan, Shabeesh; Hisano, Yasuko; Nozaki, Yayoi; Ohba, Hisako; Toyoshima, Manabu; Shimamoto, Chie; Tabata, Chinatsu; Wada, Yuina; Yoshikawa, Takeo
ABSTRACT: The present study describes the hair growth-promoting effects of sodium thiosulfate (STS), a widely used compound, in mice. STS accelerated hair growth in the "telogen model", suggesting that it stimulates telogen hair follicles to reenter the anagen phase of hair growth. In the same model, STS potentiated hair growth in an additive manner with minoxidil (MXD), a drug used for the treatment of androgenic alopecia. Furthermore, in the "anagen model", STS promoted hair growth, probably by promoting hair follicle proliferation. Since STS elevated the skin surface temperature, its hair growth-promoting activity may be partly due to vasorelaxation, similar to MXD. In addition, STS is known to generate a gaseous mediator, H2 S, which has vasorelaxation and anti-inflammatory/anti-oxidative stress activities. Therefore, STS and/or provisionally its metabolite, H2 S, may aid the hair growth process. Collectively, these results suggest that salts of thiosulfate may represent a novel and beneficial remedy for hair loss. Graphical abstract: : We found the hair growth-promoting effects of sodium thiosulfate (STS) in mice. STS may represent a beneficial remedy for hair loss.